ChemInform Abstract: Molecular Iodine‐Mediated Difunctionalization of Alkenes with Nitriles and Thiols Leading to β‐Acetamido Sulfides. Issue 31 (14th July 2016) - Cui, Huanhuan; Liu, Xiaoxia; Wei, Wei; Yang, Daoshan; He, Chenglong; Zhang, Tiantian; Wang, Hua
Abstract: A three‐component reaction of olefins, thiols, and aliphatic nitriles with molecular iodine as catalyst is presented to give β‐acylamidosulfides.